Statistical Prediction in Accordance with the Continuous Forces of Momentum - صالح د.أحمد يوسف (Dirasat in Economics and Business, 1982)
All statistical methods of prediction de- pend on the relation between the event in question (the dependent variable) and the main factors of that event (the independent variables). These methods, however, are an inaccurate basis of prediction for social and economic phenomena for the following rea sons: 1. These methods of prediction assume that the effects of the main factors are constant, which is at variance with the dynamic behaviour of these social and economic phenomena. 2. Macro systems of production imply a large number of factors which cannot be subsumed under specific groups owing to their individual properties (e.g. total agricultural production). 3. There are effective factors which are difficult to control or evaluate (for in stance, variable weather conditions). 4. Some production systems have a high degree of technological elasticity, which leads to a monotonic increase in the effects of the factors. 5. In macro production systems use can be made of a number of continuous forces of momentum which carry forward production along its general trend. There are great difficulties involved in any attempt to suddenly interrupt the effects of these factors, this arising from their dynamic physical nature. 6. Likewise, it is unfeasable, over a few years, to change the general production trend by doubling the effect of the fac tors due to the limited nature of eco nomic resources. Making use of the properties of the continuous forces of momentum, we can establish a more reliable prediction trend.